Glycoconjugated Rhenium(I) and 99m‐Technetium(I) Carbonyl Complexes from Pyridyltriazole Ligands Obtained by "Click Chemistry". Issue 36 (25th November 2014) - Czaplewska, Justyna A.; Theil, Frank; Altuntas, Esra; Niksch, Tobias; Freesmeyer, Martin; Happ, Bobby; Pretzel, David; Schäfer, Hendrik; Obata, Makoto; Yano, Shigenobu; Schubert, Ulrich S.; Gottschaldt, Michael
Abstract: A series of pyridyltriazole ligands containing sugar moieties have been prepared by copper(I)‐mediated 1, 3‐dipolar cycloaddition ("click" reaction) of azides functionalized withD ‐glucose, D ‐galactose, D ‐mannose, D ‐xylose as well asD ‐maltose residues, and 2‐ethynylpyridine as alkyne. The peracetylated saccharide residues as well as their water‐soluble deprotected derivatives were treated with Re(CO)5 Cl to obtain the corresponding mononuclear rhenium(I) carbonyl complexes [LRe(CO)3 Cl]. For comparison, one Re I complex bearing a tert ‐butylbenzyl residue instead of a sugar moiety as well as two dinuclear rhenium complexes derived from a branched ligand containing two pyridyltriazole units were prepared. The structure and integrity of the ligands and complexes was established by NMR, IR, UV/Vis and fluorescence spectroscopy, mass spectrometry, and by elemental analysis. Coordination of the metal ion occurred by both the pyridyl nitrogen atoms and one of the triazole nitrogen atoms. Upon treatment with an excess of histidine, the Re I complexes were stable for only 2.5 h. After a longer period (24 h) ligand exchange was detected by HPLC measurements. In contrast, a complex labeled with 99m Tc was found to be stable for up to 24 h against an excess of histidine. Cytotoxicity was screened for all Re I complexes against HepG2 cells using a concentration of 100 μM . All sugar‐functionalized complexes were found to be nontoxic, except for the complex derived from the pyridyl ( tert ‐butylbenzyl)‐triazole, which exhibited remarkable toxicity. Abstract : A series of pyridyltriazole ligands containing sugar moieties and their corresponding Re(I) complexes were synthesized and characterized. Stability tests against histidine showed that the complexes are stable up to 2.5 h; the 99m Tc‐labeled complex was stable up to 24 h. All sugar‐based Re I complexes were nontoxic against HepG2 cells; in contrast, the Re I complex without a carbohydrate moiety was toxic.